A Multistage Process Model of How a Person Who Currently Injects Drugs Comes to Assist Persons Who Do not Inject with Their First Injections - Des Jarlais, Don C.; Arasteh, Kamyar; Barnes, David M.; Feelemyer, Jonathan; Berg, Hayley; Raag, Mait; Talu, Ave; Org, Greete; Tross, Susan; Uuskula, Anneli (Frontiers in Sociology, 2021)
Injecting drugs for the first time almost always requires assistance from an experienced person who injects drugs (PWID). While there has been moderate amount of research on PWID who assist with first injections, most of this research has focused on identifying characteristics of PWID who assist with first injections. We do not have a formal model that describes how the minority of PWID come to assist do so, while the majority never assist. Through comparison of persons who did or did not recently assist with first injections using data from PWID in Tallinn, Estonia (N=286) and Staten Island, New York City (N=101), we developed a formal multi-stage model of how PWID come to assist with first injections. The model had a primary pathway 1) of engaging in “injection promoting” behaviors, 2) being asked to assist, and 3) assisting. Statistical testing using odds ratios showed participation in each stage was strongly associated with participation in the next stage (all odds ratios >3.0) and the probabilities of assisting significantly increased with participation in the successive stages. We then used the model to compare engagement in the stages pre- vs. post participation in an intervention, and to compare persons who recently assisted to persons who had assisted in the past but had not recently assisted and to persons who had never assisted. Advantages of a formal model for how current PWID come to assist with first injections include: facilitating comparisons across different PWID populations and assessing strengths and limitations of interventions to reduce assisting with first injections.